Kinetics of the soluble urokinase plasminogen activator receptor (suPAR) in cirrhosis - Garnæs, Emilie (PLoS One, 2019)
BACKGROUND: The soluble urokinase plasminogen activator receptor (suPAR) is related to hepatic inflammation and fibrosis and has been suggested to participate in the development of liver cirrhosis. Therefore, the aim of the current study was to measure the concentration of suPAR in the hepatic vein of cirrhotic patients during a liver vein catheterization to identify a possible hepatic suPAR generation. Furthermore, we explored if suPAR levels were associated with the degree of cirrhosis and liver dysfunction. METHODS AND PATIENTS: We included 105 cirrhotic patients and 19 liver-healthy controls. Blood was sampled from the hepatic vein and the femoral artery and suPAR was measured by enzyme-linked immunosorbent assay. RESULTS: We identified significantly higher median suPAR concentrations among the cirrhotic patients (7.2 ng/ml in the hepatic vein; 6.8 ng/ml in the femoral artery) compared to the controls (2.6 ng/ml, respectively, p-values <0.001). However, the median hepatic suPAR formation was 0.0 ng/ml in both groups. We observed significantly increasing suPAR levels according to higher Child classes (4.5 ng/ml, 6.9 ng/ml and 9.0 ng/ml, Child A, B, C respectively; p-value<0.001), and significantly higher median suPAR concentrations in patients with ascites versus patients without ascites (8.1 ng/ml versus 5.3 ng/ml, respectively, p-value<0.001). suPAR levels were significantly related to bilirubin (r = 0.48, p<0.001), the hepatic venous pressure gradient (r = 0.39, p<0.001), the cardiac index (r = 0.24, p = 0.02) and the plasma volume (r = 0.33, p = 0.001), whereas suPAR levels were significantly inversely related to albumin (r = -0.59, p<0.001), plasma coagulation factors (r-0.39, p<0.001), the mean arterial pressure (r = -0.28, p = 0.004), the systemic vascular resistance (r = 0.26, p = 0.007), the indocyanine green clearance (r = -0.51, p<0,001) and the galactose elimination capacity (r = -0.39, p<0.001). CONCLUSION: We identified elevated suPAR concentration in cirrhotic patients, which correlated significantly with the degree of cirrhosis and liver failure, but we were not able to demonstrate hepatic suPAR generation per se. This suggests that further investigations of the source of suPAR in cirrhotic patients need to be undertaken.